HKUST-1-MOF–BiVO4 hybrid as a new sonophotocatalyst for simultaneous degradation of disulfine blue and rose bengal dyes: optimization and statistical modelling. Issue 66 (27th June 2016) - Mosleh, S.; Rahimi, M. R.; Ghaedi, M.; Dashtian, K.
Abstract : A new hybrid material composed of BiVO4 and HKUST-1 MOF (HKUST-1-MOF–BiVO4 ), which is active under blue light irradiation, was synthesized and characterized by XRD, FE-SEM, BET, BJH, EDS and DRS analysis. Abstract : A new hybrid material composed of BiVO4 and HKUST-1 MOF (HKUST-1-MOF–BiVO4 ), which is active under blue light irradiation, was synthesized and characterized by XRD, FE-SEM, BET, BJH, EDS and DRS analysis. Subsequently, this sonophotocatalyst was applied for simultaneous sonophotodegradation of disulfine blue (DB) and rose bengal (RB). The influence of conventional variables such as initial dyes concentration (5–45 mg L −1 ), HKUST-1-MOF–BiVO4 mass (0.1–0.3 g L −1 ), flow rate (40–120 mL min −1 ), pH (2–10) and time of irradiation (5–25 min) upon sonophotocatalytic degradation efficiency was studied by central composite design (CCD). The results analysis revealed that optimum values for the variables studies were found to be 0.2 g L −1, 30 and 30 mg L −1, 80 mL min −1, 6 and 20 min for the HKUST-1-MOF–BiVO4 mass, initial concentration of DB and RB, flow rate, pH and irradiation time, respectively. Under the optimum conditions, the sonophotocatalytic DB and RB degradation percentages at desirability function value of 1.0 were found to be 99.98% and 98.76%, respectively. A kinetics study revealed that the Langmuir–Hinshelwood (L–H) kinetics model was well fitted to the experimental data. Finally, contributions from sonocatalysis and photocatalysis using synergy index and the stability of HKUST-1-MOF–BiVO4 were investigated.